DUAL MONETARY INSTRUMENTS’ IMPACT ON THE PERFORMANCE AND STABILITY OF JAKARTA ISLAMIC INDEX - Azizi, Bazari Azhar (Journal of Islamic Monetary Economics and Finance, 2018)
The monetary instruments and capital market are closely related as these tools are operating in the money market. The influence of the monetary policy to the stocks and indexes’ performance has been the research interest in the previous literature. The monetary policies along with its’ instruments are transmitted not only in banking lending channel to affect the economic growth but also in the balance sheet channel. However, the conventional tools and policies are not adhering the sharia tenets. Hence, the sharia-compliance monetary system is emanated in Muslim majority countries, including Indonesia. Additionally, this establishment of policy is coupled with the emergence of the Islamic capital market in Indonesia. Thus, the analysis of the impact of either Islamic or conventional monetary system on the Islamic capital market in Indonesia that represented by the Jakarta Islamic Index (JII) is essential to look at its’ furthers effect on financial market growth. This study examines the impact of the Islamic and conventional monetary variables on the performance of the Jakarta Islamic Index in Indonesia. It also investigates the stability of the JII under the occurrence of the shock derived from the monetary instruments. Monthly closing value of the JII, conventional or interest rate, Islamic policy rate, and monetary base are assessed to address the research objectives in this paper. This study employs the VAR-VECM and Granger analysis to analyse the phenomenon. The monetary policy transmission mechanism through the financial market channel is the main channel that will be investigated in this paper. The study comprises of introduction, literature review, methodology, and lastly the discussion and conclusion.